Isolation and Characterization of 11 Polymorphic Microsatellite Markers Developed for Orthops palus (Heteroptera: Miridae). Issue 1 (27th February 2016) - Atiama, M.; Delatte, H.; Deguine, J.-P.
Abstract: Miridae (Hemiptera: Heteroptera: Cimicomorpha), or plant bugs, are one of the most diverse and species-rich families of insects. Most of them are phytophagous, but some are insect predators and used for biocontrol. Among this family, the mango bug, Orthops palus (Taylor 1947), is one of the most important pest of mango in Reunion Island. We developed 11 polymorphic microsatellite loci to study the population genetics of this pest species. The microsatellite markers were characterized by genotyping 78 field-collected insects sampled at different localities in Reunion Island. The number of alleles per locus ranged from 1 to 13 and heterozygosity levels ranged between 0.40 and 0.94. Several loci were not at Hardy–Weinberg equilibrium for the tested populations. These markers are the first to be developed for a species of the genus Orthops.